Pengaruh liquidity dan board gender serta profitability terhadap corporate social responsibility disclosure pada perusahaan yang terdaftar di bursa efek indonesia - Sisca Sinthia Anwar; Djoko Setyadi; Rizky Yudaruddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Sisca Sinthia Anwar, 2017. Influence of liquidity and board gender andprofitability of the corporate social responsibility disclosure in companies listed on the Indonesia Stock Exchange. This study aims to determine the negative influence liquidity of the corporate social responsibility disclosure, know the positive influence of gender on the board corporate social responsibility disclosure and to know the positive impact the profitability of the corporate social responsibility disclosure. This study uses panel data is the combined data time-series and cross-section with a sample of 21 mining companies listed on the Indonesia Stock Exchange in 2010 to 2015. The data were analyzed with panel data regression Eviews Program 8 and using a fixed effect model (FEM ). The results of this study indicate that liquidity proxied in current ratio significant positive effect on corporate social responsibility disclosure and board gender proxy in the female on board had a positive influence not significant corporate social responsibility disclosure and profitability (return on equity) have a positive effect but no significant effect on corporate social responsibility disclosureKeywords: Current Ratio, Female on Board, Return on Equity and Corporate Social Responsibility Disclosure